An In vitro, nonexperimental, exploratory research for the development of a guidance system to identify dental implant system used in India based on their radiographic appearance - Sayali Ulhas Kute; Amit Arvind Agrawal; Nilima Prakash; Meenal N Gulve (Wolters Kluwer Medknow Publications, 2023)
Introduction: Identifying an osseointegrated dental implant could become vitally important in case some other clinician tries to restore it and plays a vital role in forensic odontology. However, existing ways to identify them are very crude and nonspecific. In addition, they are not focusing on implants used frequently in India. Aims: The aim of this study was to design a guidance system to identify different implant systems and their subtypes used in India and to evaluate the efficiency of this guidance system to identify an unknown dental implant. Materials and Methods: Radiographs of the 15 most common dental implant systems used in India were analyzed and categorized based on their morphological appearance under the headings. Nontapered or tapered/threaded or not, neck design, thread length, shape, etc., were observed on intraoral periapical radiographs, and a guidance system in the form of a flow chart was made. Based on the flow chart, 15 randomized assessor-blinded radiographs were tested for the accuracy of the guidance system that was developed. The Chi-square test was used at a 95% confidence interval to determine the accuracy of the guidance system used for the identification of assessor-blinded radiographs. Results: The newly designed dental implant identification guidance system effectively identified 14 out of 15 unknown implant radiographs among implant systems and subtypes used in this study. Nonparametric Chi-square test was applied and the results were highly significant (P < 0.05). Conclusions: The guidance system developed has the potential to identify the implant system mentioned in this study based on its radiographic appearance.